Higenamine Attenuates Neuropathic Pain by Inhibition of NOX2/ROS/TRP/P38 Mitogen-Activated Protein Kinase/NF-ĸB Signaling Pathway - Yang, Bing; Ma, Shengsuo; Zhang, Chunlan; Sun, Jianxin; Zhang, Di; Chang, Shiquan; Lin, Yi; Zhao, Guoping (Frontiers in Pharmacology, 2021)
Oxidative stress damage is known as one of the important factors that induce neuropathic pain (NP). Using of antioxidant therapy usually achieve an obvious curative effect to alleviate NP. Previous pharmacological studies have shown that higenamine (Hig) performs to be an antioxidant and anti-inflammatory. However, the protective effect and mechanism of Hig on NP is still unclear. This study mainly evaluated the changes in reactive oxygen species (ROS) level, lipid peroxidation, and antioxidant system composed of SOD and GSH through chronic constrict injury (CCI) model rats and t-BHP-induced schwann cell (SC) oxidative stress model. The expressions of inflammatory factors tumor necrosis factor- alpha (TNF-α) and interleukin-6 (IL-6) were also assessed. The possible molecular mechanism of Hig in the treatment of NP was explored in conjunction with the expression of mitochondrial apoptosis pathway and NOX2/ROS/TRP/P38MAPK/NF-ĸB pathway related indicators. Hig showed substantial antioxidant and anti-inflammatory properties both in in vivo and in vitro. Hig significantly reduced the up-regrated levels of ROS, malondialdehyde (MDA), TNF-α, and IL-6, and increased the levels of SOD and GSH, which rebalanced the redox system and improved the survival rate of cells. In the animal behavioral test, it was also observed that Hig relieved the CCI-induced pain, indicating Hig performed a pain-relief effect. Our research results suggested that Hig improved NP-induced oxidative stress injury, inflammation and apoptosis, and this neuroprotective effect may be related to the NOX2/ROS/TRP/P38MAPK/NF-ĸB signaling pathway.